Penerapan Ice Breaking dalam Meningkatkan Semangat Belajar Mahasiswa PGMI Semester 1 di Universitas Islam Tribakti Lirboyo - Ahmad Zulfa Khotmi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Maintaining students’ learning motivation, particularly during the initial semester, presents a significant challenge in higher education, especially for those with pesantren (Islamic boarding school) backgrounds who are adapting to a new academic environment. This study aims to explore the role of ice breaking techniques in fostering and sustaining learning enthusiasm among first-semester students in the PGMI (Primary School Teacher Education) Program at Universitas Islam Tribakti Lirboyo. Employing a qualitative case study approach, data were collected through participatory observation, in-depth interviews, and documentation involving students actively participating in lectures. Thematic analysis was conducted through data reduction, presentation, and conclusion drawing. The findings reveal that ice breaking activities positively contribute to creating a relaxed classroom atmosphere, strengthening social bonds among students, and enhancing active participation in learning. Students reported feeling more prepared, engaged, and motivated after participating in ice breaking sessions. Moreover, these techniques effectively serve as a psychological bridge from the rigorous pesantren routine to the more interactive and dialogical demands of university learning. These results are supported by humanistic learning theories and motivational frameworks, which emphasize the importance of emotionally supportive learning environments. The study recommends the systematic integration of ice breaking activities into higher education learning strategies, particularly in pesantren-based institutions, to foster more humanistic, participatory, and adaptive learning settings